Crystal structure and Hirshfeld surface analysis of 8-benzyl-1-[(4-methylphenyl)sulfonyl]-2,7,8,9-tetrahydro-1H-3,6:10,13-diepoxy-1,8-benzodiazacyclopentadecine ethanol hemisolvate - Gleb M. Burkin; Elizaveta A. Kvyatkovskaya; Victor N. Khrustalev; Khudayar I. Hasanov; Nurlana D. Sadikhova; Mehmet Akkurt; Ajaya Bhattarai (Acta Crystallographica Section E: Crystallographic Communications, 2024)
The asymmetric unit of the title compound, 2C31H28N2O4S·C2H6O, contains a parent molecule and a half molecule of ethanol solvent. The main compound stabilizes its molecular conformation by forming a ring with an R12(7) motif with the ethanol solvent molecule. In the crystal, molecules are connected by C—H...O and O—H...O hydrogen bonds, forming a three-dimensional network. In addition, C—H...π interactions also strengthen the molecular packing.